Measuring speed compliance on a university campus: A case study at UTAR Kampar - Chee, He Wid; Salamon, Brangiss; Sim, Zheng Lin; Sin, Yi Yang (2025)
The research examines speed compliance of vehicles at the Universiti Tunku Abdul Rahman (UTAR) Kampar campus by studying straight roads and curved roads as well as parking zones. The research project examines both the level of speed limit compliance among campus vehicles and the zones where speeding occurs most frequently, and it assesses existing speed reduction methods. The researchers conducted mechanical speed measurements with radar guns at 16 checkpoints during four time periods of each day. The majority of vehicles do not follow speed restrictions as results show main roads having average speeds above 30 km/h and parking areas exceeding 15 km/h. During peak traffic times the rate of speed compliance gets higher since drivers display more caution on busy roads. The research results indicate that campus road security requires better enforcement efforts together with educational initiatives and structural enhancements including better signage along with extra speed reduction features. The research provides essential information which campus authorities should use to develop targeted plans to enhance safer driving practices and protect campus users.